2020
DOI: 10.1186/s13071-020-04341-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Fludora® Fusion (a mixture of deltamethrin and clothianidin) for indoor residual spraying against pyrethroid-resistant malaria vectors: laboratory and experimental hut evaluation

Abstract: Background A new generation of IRS insecticides which can provide improved and prolonged control of pyrethroid-resistant malaria vector populations are being developed. Fludora® Fusion is a new IRS insecticide containing a mixture of deltamethrin and clothianidin, a neonicotinoid. Methods The efficacy of Fludora® Fusion IRS was evaluated over 11–12 months on concrete and mud substrates in laboratory bioassays and experimental huts against wild free-flying pyrethroid-resistant Anopheles gambiae (sensu lato) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 17 publications
5
49
0
Order By: Relevance
“…By contrast, our study demonstrated longer residual efficacy of VECTRON T500 in laboratory cone bioassays with the susceptible Kisumu strain on mud block substrates (> 80% mortality for 18 months) compared to cement block substrates (> 80% mortality for 6 months). This corroborates our previous findings in similar studies with another IRS insecticide 27 . The improved residual efficacy with the mud block substrates could be attributed to the addition of a small amount of cement to the mud paste during the preparation of the block substrates, in line with local practices in some areas in Benin, making the substrates more stable and less porous.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…By contrast, our study demonstrated longer residual efficacy of VECTRON T500 in laboratory cone bioassays with the susceptible Kisumu strain on mud block substrates (> 80% mortality for 18 months) compared to cement block substrates (> 80% mortality for 6 months). This corroborates our previous findings in similar studies with another IRS insecticide 27 . The improved residual efficacy with the mud block substrates could be attributed to the addition of a small amount of cement to the mud paste during the preparation of the block substrates, in line with local practices in some areas in Benin, making the substrates more stable and less porous.…”
Section: Discussionsupporting
confidence: 93%
“…This delayed activity could be attributed to its mechanism of action; broflanilide has to be metabolized to its active form, desmethyl-broflanilide, before binding to its site of action 18 . Delayed mosquito mortality effects has also been observed with clothianidin 14 , 27 and chlorfenapyr 15 , 28 which are the main active ingredients in newly approved IRS insecticide formulations and insecticide treated nets for malaria vector control 13 . While the relative impact of such slow acting insecticides is yet to be fully assessed, modelling studies have suggested that development of resistance to these insecticides may be slower compared to fast-acting neurotoxic insecticides 29 .…”
Section: Discussionmentioning
confidence: 99%
“… CDC LT US Centers for Disease Control light trap, HLC human landing collection, IRS indoor residual spraying, PM pirimiphos-methyl a From 2016 pre-intervention census[ 18 ] …”
Section: Methodsmentioning
confidence: 99%
“…The first of these products to receive WHO recommendation as a malaria vector control tool was a microencapsulated formulation of the organophosphate insecticide pirimiphos-methyl (PM): Actellic® 300CS (Syngenta AG, Basel, Switzerland). While initial results showing the impact of Actellic and other 3GIRS products have been encouraging [ 12 18 ], questions remain about where and how to best deploy them to maximize their impact.…”
Section: Introductionmentioning
confidence: 99%
“…Cement and mud block substrates used in cone bioassays were prepared and treated using similar methods described in previous studies by our group 37 . Blocks were moulded in Petri dishes (9cm diameter and 5mm thick) and dried at 27 °C ±2 °C and 80 ±10% RH for 30 days before insecticide application.…”
Section: Preparation and Treatment Of Block Substratesmentioning
confidence: 99%